Perlindungan Hukum Bagi Dalam Tindak Pidana Korupsi Saksi - de Fretes, Petra Jon; Hehanussa, Deassy Jacomina Anthoneta; Hattu, Jacob (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Legal protection for witnesses in corruption crimes is a form of service that must be provided by the government to witnesses to provide a sense of security.Purposes of the Research: The purpose of this study is to analyze and discuss legal protection for witnesses in corruption crimes according to Law Number 13 of 2006 concerning the Protection of Witnesses and Victims and to analyze and explain the mechanisms for providing legal protection to witnesses and victims by the LPSK.Methods of the Research: The method used is normative juridical with the Statute Approach, Conceptual Approach and Case Approach, and uses primary, secondary and tertiary legal materials.Results of the Research: The results of this study indicate that legal protection for witnesses in criminal acts of corruption according to Law No. 13 of 2006 must be given to witnesses since they are appointed as witnesses. This is to protect witnesses from actions outside the law that can harm witnesses. Then the mechanism for providing legal protection for witnesses should be that legal protection is a right for witnesses. Therefore, all mechanisms or procedural forms in providing protection must be eliminated by taking into account the urgency of providing legal protection for witnesses.